Pengaruh Literasi Keuangan, Financial Technology (Fintech) Dan Locus Of Control Terhadap Penggunaan Paylater Pada Mahasiswa Universitas Dharma Andalas - Nadya Variza; Henny Sulistianingsih (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research aims to determine the influence of financial literacy, financial technology, and locus of control on the use of paylater among Dharma Andalas University students. The population in this study was active students at Dharma Andalas University, with samples taken using nonprobability sampling, so the sample was 138 people. Data was obtained by distributing questionnaires and then processed and tested using the SPSS (Statistical Package for Social Science) application. From the research conducted, it is known that based on the results of hypothesis testing, it shows 1). Financial literacy has a positive and significant effect on the use of paylater, 2). Financial Technology has a positive and significant effect on the use of paylater, 3Locus of Control has a positive and significant effect on the use of paylater among students, 4). Financial literacy, financial technology and locus of control have a positive and significant effect on the use of paylater among students.